Financial liberalization, growth, productivity and capital accumulation: The case of European integration - Agnieszka Gehringer (FIW - Research Centre International Economics, 2012)
In the present contribution, we concentrate on the process of financial liberalization in a specific context of European economic and monetary integration. We implement de facto and de jure measures of financial liberalization and find that formal aspects of financial openness generate a strongly positive impact on economic growth and its sources, productivity growth and capital accumulation. Moreover, there is evidence of a positive contribution to the process stemming from the EU membership, while no substantial effect comes from the euro adoption. Finally, we investigate the effects from financial integration on country groups within the EU.
Keywords: F41; F36; F43; 330; Financial integration; economic growth; productivity; European integration